1981
DOI: 10.1111/j.1432-1033.1981.tb05553.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Thiol Residues of Pyridine Nucleotide Transhydrogenase from Azotobacter vinelandii. Activity Modulation by the Divalent Thiol Reagent p-Aminophenylarsenoxide

Abstract: 1. Purified pyridine nucleotide transhydrogenase from Azotobacter vinelandii contains three thiol residues as judged by titration with 5,5'-dithiobis(2-nitrobenzoic acid) under denaturing conditions.2. In the native conformation of the transhydrogenase only a single thiol residue is titrated. Modification of this exposed thiol does not influence transhydrogenase activity.3. The two less exposed thiol residues can be reacted in part with either p-chloromercuribenzoate or N-ethylnmleimide. Modification of one re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The amino acid composition of the STH as deduced from the sequence was found to be very similar to that determined by hydrolysis of the purified protein by Voordouw et al and Middelditch et al [11,12]. Titration experiments had shown that the enzyme contained three thiol residues, one of which was exposed to solvent [13], however, four cysteine residues are found in the sequence.…”
Section: Resultssupporting
confidence: 73%
“…The amino acid composition of the STH as deduced from the sequence was found to be very similar to that determined by hydrolysis of the purified protein by Voordouw et al and Middelditch et al [11,12]. Titration experiments had shown that the enzyme contained three thiol residues, one of which was exposed to solvent [13], however, four cysteine residues are found in the sequence.…”
Section: Resultssupporting
confidence: 73%
“…The amino acid composition of the STH as deduced from the sequence was found to be very similar to that determined by hydrolysis of the puri¢ed protein by Voordouw et al and Middelditch et al [11,12]. Titration experiments had shown that the enzyme contained three thiol residues, one of which was exposed to solvent [13], however, four cysteine residues are found in the sequence.…”
Section: Cloning and Sequence Analysis Of The Sth Gene Of A Vinelandiimentioning
confidence: 72%
“…The carbonyl carbon atom is not given, but it was found to resonate at 171.6 ppm. 6 Only determined for protonated carbon atoms. NOE's are given in parentheses.…”
Section: Resultsmentioning
confidence: 99%